Pendampingan Tahap Awal Riset Pasar Melalui Survey Kepuasan Pelanggan Pada Bisnis Kuliner Online “Nanreku” Di Makassar Sulawesi Selatan - Sari, A Ratna; Hasma, Hasma; Selfi, Selfi; Jusmawati, Jusmawati (Universitas Patria Artha, 2025)
This Community Service Activity aims to provide understanding to the community, especially MSME business actors, about the importance of conducting Market Research, namely by conducting Customer Satisfaction surveys in an effort to develop their business. This activity is carried out by carrying out initial observation methods and providing outreach to raise awareness of business owners/managers about the benefits and utilization of marketing research as well as conducting pretests and posttests as evaluation material to see the increase in knowledge of business owners before and after the outreach.